Determination of Kamlet–Taft parameters for selected solvate ionic liquids. Issue 19 (28th April 2016) - Eyckens, Daniel J.; Demir, Baris; Walsh, Tiffany R.; Welton, Tom; Henderson, Luke C.
Abstract : The normalised polarity E NT and Kamlet–Taft parameters of recently described solvate ionic liquids, composed of lithium bis(trifluoromethyl)sulfonimide (LiTFSI) in tri- (G3TFSI ) or tetraglyme (G4TFSI ) have been determined and compared to the parent glyme (G3 andG4 ). Abstract : The normalised polarity E NT and Kamlet–Taft parameters of recently described solvate ionic liquids, composed of lithium bis(trifluoromethyl)sulfonimide (LiTFSI) in tri- (G3TFSI ) or tetraglyme (G4TFSI ) have been determined and compared to the parent glyme (G3 andG4 ). We show that these solvate ionic liquids have a high polarity (G3TFSI, ( E NT) = 1.03;G4TFSI, ( E NT) = 1.03) and display very high electron pair accepting characteristics (G3TFSI, α = 1.32;G4TFSI, α = 1.35). Molecular dynamics simulations suggest that the chelated lithium cation is responsible for this observation. The relatively small hydrogen bond acceptor ( β ) values for these systems (G3TFSI, β = 0.41;G4TFSI, β = 0.37) are thought to be due primarily to the TFSI anion, which is supplemented slightly by the glyme oxygen atom. In addition, these solvate ionic liquids are found to have a high polarisability (G3TFSI, π * = 0.94;G4TFSI, π * = 0.90).